Designing Business Architecture and Application of E-Collaboration for Small and Medium Enterprises in Indonesia Using Service Oriented Architecture - Cindy Kristiya Himawan (President University, 2016)
As one of the factors supporting the nation's economy, the existence of Small and Medium Enterprises (SMEs) need attention and support, both in terms of guidance from the government, aid loans from banks and use of information technology. Given some limitations such as limited SMEs in marketing, interacting with other business and limitations in the procurement of information technology, it is necessary to have a platform for SMEs to conduct their business activities and interact with other SME or external parties, in an internet-based application called e-collaboration. By utilizing the concept of service-oriented architecture (Service Oriented Architecture), this paper resulted in the design of conceptual business architecture and technology architecture support. The author conducted research in the field to determine the condition of the SMEs and formulate appropriate business needs to define the business architecture. Business architecture defines the business component SMEs and collaborative business processes that occur in the environment of these SMEs. Business architecture is translated into a conceptual architecture for defining design technology that will be used to support the use of information technology shared services to run business collaboration. The design of e-collaboration application that is able to define all components produced in small business and accommodate the needs of the overall business processes for SMEs both the internal business processes and business collaboration process with external parties. To support the business collaboration with external parties, we need to define the service contract and service level agreement which include the procedure and process standarization to exchange the data. For validation, the author perform an inspection of the functionality owned by the e-collaboration applications which will be made into a a service evaluation matrix and traceability matrix to match if the design has been constructed in accordance with business needs. In addition, a simple prototype will be built to ensure the resulting design can be implemented in accordance with business needs